Situated and mobile displays for reflection on shopping and nutritional choices - Reitberger, Wolfgang; Spreicer, Wolfgang; Fitzpatrick, Geraldine (Personal and ubiquitous computing, 2014)
In this paper, we explore the use of peoples’ shopping data to raise awareness and to enable reflection about nutrition. In order to ground our Nutriflect approach, we conducted 125 structured interviews in grocery stores. Informed by the results of this exploratory study, we designed a system that shows a household’s collective food consumption patterns via situated displays in the home and through mobile devices in-store. The system aimed to minimize the need for manual entry of nutrition-related data by the users. To evaluate our system, we conducted a 4-week field study in eight households with 21 inhabitants and situated in-store shopping inquiries with a subset of 9 of these users, using actual shopping data from participants. In these studies, we identified issues regarding the interaction design of Internet of Things applications and explored the use of complementary distributed displays to provide tailored cues in context. The approach taken showed the potential to foster reflection about shopping and nutritional choices and for integration with people’s everyday practices.